Computer-assisted, minimally invasive transforaminal lumbar interbody fusion: One surgeon's learning curve A STROBE-compliant article. Issue 27 (July 2018) - Xu, Yun-Feng; Le, Xiao-Feng; Tian, Wei; Liu, Bo; Li, Qin; Zhang, Gui-Lin; Liu, Ya-Jun; Yuan, Qiang; He, Da; Mao, Jian-Ping; Xiao, Bin; Lang, Zhao; et al.
Abstract : Abstract: Minimally invasive (MI) transforaminal lumbar interbody fusion (TLIF) is a challenging technique with a long learning curve. We combined computer-assisted navigation and MI TLIF (CAMISS TLIF) to treat lumbar degenerative disease. This study aimed to evaluate the learning curve associated with computer-assisted navigation MI spine surgery (CAMISS) and TLIF for the surgical treatment of lumbar degenerative disease. Seventy four consecutive patients with lumbar degenerative disease underwent CAMISS TLIF between March 2011 and May 2015; all surgeries were performed by a single surgeon. According to the plateau of the asymptote, the initial 25 patients constituted the early group and the remaining patients comprised the latter group. The clinical evaluation data included operative times, anesthesia times, intraoperative blood losses, days until ambulation, postoperative hospital stays, visual analog scale (VAS) leg and back pain scores, Oswestry disability index (ODI) values, Macnab outcome scale scores, complications, radiological outcomes, and rates of conversion to open surgery. The complexity of the cases increased over the series, but the complication rate decreased (12.00%–6.12%). There were significant differences between the early and late groups with respect to the average surgical times and durations of anesthesia, but no differences in intraoperative blood losses, days until ambulation, postoperative hospital stays, complication rate, VAS, ODI, Macnab outcome scale scores, or solid fusion rates. There was no need for conversion to open procedures in either group. Our study showed that a plateau asymptote for CAMISS TLIF was reached after 25 operations. The later patients experienced shorter operative times and anesthesia durations.